GATT, WTO dan hasil Uruguay Round - Kartadjoemena, H. S. (Jakarta : Penerbit Universitas Indonesia (UI-Press), 1997)
Indonesia's foreign and economic policies regarding international trade
Includes bibliographical references and index
Keywords: General Agreement on Tariffs and Trade (Organization); Cormmercail policy; Tariff